HOW AN EFL TEXTBOOK TEACH LEARNERS’ PRAGMATIC SKILL - Emiliasari, Raynesa Noor; Kailani, Ahmad; Lukmana, Iwa (CALL, 2024)
Abstract As a language learning resource, an English as a foreign language (EFL) or English as a second language (ESL) textbook plays a pivotal role in students’ pragmatic development. There has been a plethora of studies conducted to evaluate the quality of textbooks across the countries regarding the proportional content of pragmatic uses. However, there is still no evidence of the study in Indonesia. Thus, to fill this void, the study aims to explore types of speech acts included in an EFL coursebook for senior high school students and to what extent those speech acts meet students’ learning needs. This study employs a qualitative content analysis method, with one nationally mandated English textbook for senior high school students chosen and analysed. The analysis included categorizing dialogues in the textbook using Searle's (1976) Speech Act Theory, which comprises directive, commissive, representative/assertive, declarative, and expressive speech acts. The research findings indicate that the pragmatic content in the coursebook is still inadequate. This inadequacy may affect students’ pragmatic development since proportional use of all types of speech acts would help learners use an appropriate speech act in an appropriate social setting. There is a call for more studies on the evaluation of EFL textbooks which use textbooks from all grades at senior high school level. Keyword: EFL textbook, pragmatics, speech act analysis